Fungsi ~Tokoro, ~Teiru Tokoro, ~Ta Tokoro dan Perbandingan dengan ~Te Iru, ~Ta Bakari - Aprilani, Felicia (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 1 No 1 (2019), 2019)
ABSTRACT   In Japanese, Tokoro actually means "place", but besides that it also shows a certain time. Here I examine the meaning of the second tokoro. Tokoro is used to emphasize meaning and explain the time when an activity occurred.   The data used in this study are in the form of tokoro, teiru tokoro, ta tokoro and the comparison with the same, ta bakari, which is analyzed based on the functions and differences. In the analysis phase using the method of religion which contains some research techniques. Based on the analysis that has been done, it can be seen the difference between the two vocabulary. Practically this research is expected to be useful for foreign speakers of Japanese. Here the author hopes that after completing the nihongo bunpou course students are expected to have grammatical knowledge in Japanese then specifically after attending classes with subjects in the form of tokoro, teiru tokoro, ta tokoro and their comparison with the following, ta bakari, which is based on function and the difference so students can understand and apply it in Japanese.    Keywords: tokoro, te iru tokoro, ta tokoro, ta bakari, comparison and function